2018
DOI: 10.1016/j.bpsc.2017.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

Working Memory Training Improves Alcohol Users’ Episodic Future Thinking: A Rate-Dependent Analysis

Abstract: These data support the notion that WM training improves near-transfer task performance and may enhance the effects of EFT DD in a subset of alcohol-dependent individuals trapped within the narrowest temporal window. Rate-dependent changes highlight that we should attend to baseline performance to better identify individuals who would most benefit from an intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 51 publications
6
51
0
Order By: Relevance
“…Similar to previous studies in healthy control subjects (Dahlin et al., ; Jaeggi et al., ; Li et al., ) and other patient populations (Klingberg et al., ; Westerberg et al., ), the present study also found a statistically significant effect of repeated adaptive WM training on verbal WM capacity in AUD patients. Our results are also partly in line with the previous WM training studies indicating that WM training can improve WM function in alcohol dependence (Snider et al., ), heavy drinkers (Houben et al., ), and opioid use disorders (Rass et al., ). Similar to the current study, Rass and colleagues () also found a significant effect of WM training on the Digit Span task manifested as improvement in backward score with no effect on forward score.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to previous studies in healthy control subjects (Dahlin et al., ; Jaeggi et al., ; Li et al., ) and other patient populations (Klingberg et al., ; Westerberg et al., ), the present study also found a statistically significant effect of repeated adaptive WM training on verbal WM capacity in AUD patients. Our results are also partly in line with the previous WM training studies indicating that WM training can improve WM function in alcohol dependence (Snider et al., ), heavy drinkers (Houben et al., ), and opioid use disorders (Rass et al., ). Similar to the current study, Rass and colleagues () also found a significant effect of WM training on the Digit Span task manifested as improvement in backward score with no effect on forward score.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it was also shown that WM training improved impulse control in patients with methamphetamine use disorder (Brooks et al., ). Finally, in a recent study of alcohol‐dependent patients, Snider and colleagues () found that WM training improved WM as well as delay discounting task of episodic future thinking in a rate‐dependent manner (i.e., only in those with greatest impairments at baseline) (Snider et al., ). Taken together, previous studies of WM training in SUD populations have shown mixed results, with some preliminary findings indicating an effect on WM function, substance use, and impulsive behavior.…”
mentioning
confidence: 99%
“…Therapeutic approaches based on dual system models use computerized working memory training and episodic future thinking to modify delay discounting and expand the constricted temporal horizon characterizing the addictive state [162]. Such training has the strongest effects in substance-dependent individuals who display the steepest delay discounting [163].…”
Section: Impulsivities: Novel Behavioural Targets For Prevention and mentioning
confidence: 99%
“…In our study, participants completed a Serial 7s subtraction task 36 as a working memory training, and consistent with previous findings from Bickel et al 34 , individuals' delay discounting rates were significantly reduced. Connecting the dots, it is tempting to speculate that the reason why enforcing individuals' episodic future thinking reduces their delay discounting 35 is because the procedure (thinking about future episodes) triggers individuals to use working memory in simulating future events. However, the current results cannot reject alternative mechanistic possibilities; enhanced working memory may induce individuals to be more apt to simulate future rewards, or even more generally, working memory training may enhance general intelligence 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Addressing this, various cognitive training platforms (e.g., Lumosity 43 ) and potential intervention frameworks 34,35 were introduced to target multiple cognitive domains, including working memory, problem solving, and fluid reasoning. However, mixed results were reported whether or not the training effects are transferrable to other cognitive functions [44][45][46][47] .…”
Section: Discussionmentioning
confidence: 99%